Artificial Intelligence for Teacher Professional Development in Islamic Education: A Systematic Literature Review and Future Competency Framework - Samirah Samirah; Adiyono Adiyono; Eka Nur Safitri (Research Journal on Teacher Professional Development, 2025)
The development of Artificial Intelligence (AI) has transformed educational practices, including the professional development of teachers who increasingly demand pedagogic, digital, reflective, and ethical competencies. Although research on AI in education is progressing rapidly, a synthesis that specifically examines the professional development of teachers in the context of Islamic education is still limited and has not yet resulted in a comprehensive conceptual framework. This research aims to analyze research trends, identify key themes, opportunities, challenges, and formulate the Future AI-Driven Teacher Professional Development Framework as a conceptual model for teacher professional development in the digital era. The study used the Systematic Literature Review (SLR) approach based on the PRISMA 2020 guidelines by searching the literature from the Scopus, Web of Science, ERIC, ScienceDirect, and SpringerLink databases. Of the 2,384 publications identified, 112 articles met the inclusion criteria and were analyzed through thematic synthesis. The results show that AI contributes to the improvement of digital competence, pedagogic innovation, continuous professional learning, reflective practices, and learning efficiency. However, its implementation still faces challenges in the form of teacher readiness, digital infrastructure gaps, ethical governance, and data protection. This research offers a Future AI-Driven Teacher Professional Development Framework that integrates six main dimensions, namely digital competence, pedagogic innovation, professional learning, AI ethical governance, reflective practices, and integration of Islamic values. The framework makes a theoretical contribution to the professional development of teachers as well as a reference for policy formulation, training programs, and the sustainable implementation of AI in Islamic education.